Medium-Term Outcomes in Severely to Critically Ill Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (24th April 2021) - Gautam, Nandan; Madathil, Shyam; Tahani, Natascia; Bolton, Shaun; Parekh, Dhruv; Stockley, James; Goyal, Shraddha; Qureshi, Hannah; Yasmin, Sadhika; Cooper, Brendan G; Short, Jennifer; Geberhiwot, Tarekegn
Abstract: Background: The medium- and long-term effects of severe acute respiratory syndrome coronavirus 2 infection on survivors are unknown. In the current study, we assessed the medium-term effects of coronavirus disease 2019 (COVID-19) on survivors of severe disease. Methods: This is a retrospective, case series of 200 patients hospitalized across 3 large Birmingham hospitals with severe-to-critical COVID-19 infection 4–7 months from disease onset. Patients underwent comprehensive clinical, laboratory, imaging, lung function tests (LFTs), and quality of life and cognitive assessments. Results: At 4–7 months after disease onset, 63.2% of patients reported persistent breathlessness; 53.5%, significant fatigue; 37.5%, reduced mobility; and 36.8% pain. Serum markers of inflammation and organ injuries that persisted at hospital discharge had normalized on follow-up, indicating no sustained immune response causing chronic maladaptive inflammation. Chest radiographs showed complete resolution in 82.8%, and significant improvement or no change in 17.2%. LFTs revealed gas transfer abnormalities in 80.0% and abnormal spirometric values in 37.6% of patients. Compared with patients who did not experience breathlessness, those who did had significantly higher incidences of comorbid conditions and residual chest radiographic and LFT abnormalities ( P < .01 to all). For all parameters assessed and persisting symptoms there were no significant differences between patients in hospital wards and those in intensive treatment units. All patients reported a significantly reduced quality of life in all domains of the EQ-5D-5L quality-of-life measures. Conclusions: A significant proportion of severely ill patients with COVID-19 still experience symptoms of breathlessness, fatigue, pain, reduced mobility, depression and reduced quality of life 4–7 months after disease onset. Symptomatic patients tend to have more residual chest radiographic and LFT abnormalities. Abstract : A case series of 200 patients hospitalised with severe-to-critical COVID-19 found persisting breathlessness and fatigue in over half of cases 4-7 months post disease-onset, with higher comorbidities, abnormal chest radiographic evidence and LFT without enduring evidence of active disease.